Compassion fatigue in emergency care professionals - Letícia de Lima Trindade; Maiara Daís Schoeninger; Josiane Carneiro; Elisabete Maria das Neves Borges; Clarissa Bohrer da Silva; Carine Vendruscolo; Fernanda Karla Metelski (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to assess the level of compassion fatigue in healthcare professionals working in emergency services and its association with socio-professional characteristics. Methods: cross-sectional research, carried out in 2022 and 2023, with 186 healthcare workers. A socio-occupational questionnaire and the Professional Quality of Life Scale 5 were used. Results: higher averages of satisfaction with compassion were evidenced, followed by burnout syndrome and Secondary Traumatic Stress. Age and number of children were related to satisfaction with compassion. These variables and years of experience in the health field were inversely correlated with burnout scores. Furthermore, the higher the level of education, the lower the scores for Secondary Traumatic Stress. Conclusions: compassion satisfaction provides protection for most study participants, and it is important to invest in it to avoid compassion fatigue in this scenario.